2013
DOI: 10.1146/annurev-marine-120710-100849
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic and Biological Effects of Shoaling of the Oxygen Minimum Zone

Abstract: Long-term declines in oxygen concentrations are evident throughout much of the ocean interior and are particularly acute in midwater oxygen minimum zones (OMZs). These regions are defined by extremely low oxygen concentrations (<20-45 μmol kg(-1)), cover wide expanses of the ocean, and are associated with productive oceanic and coastal regions. OMZs have expanded over the past 50 years, and this expansion is predicted to continue as the climate warms worldwide. Shoaling of the upper boundaries of the OMZs acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
275
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(278 citation statements)
references
References 166 publications
2
275
0
1
Order By: Relevance
“…Oxycline shoaling increases the light intensities in the anoxic cores of the AMZs, thereby potentially stimulating the photosynthetic community. The effects of these changes on microbial communities and microbial biogeochemical cycling in AMZs are difficult to predict, although significant changes in carbon, nitrogen, and sulfur cycling are expected (27). Our data show a significant carbon supply to the anoxic core of the Pacific AMZs by SCM photosynthetic activity, and it is likely that the situation is similar in the Arabian Sea.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Oxycline shoaling increases the light intensities in the anoxic cores of the AMZs, thereby potentially stimulating the photosynthetic community. The effects of these changes on microbial communities and microbial biogeochemical cycling in AMZs are difficult to predict, although significant changes in carbon, nitrogen, and sulfur cycling are expected (27). Our data show a significant carbon supply to the anoxic core of the Pacific AMZs by SCM photosynthetic activity, and it is likely that the situation is similar in the Arabian Sea.…”
Section: Resultsmentioning
confidence: 75%
“…Global warming is expected to result in shoaling of the OMZ oxycline and overall expansion of OMZ volumes (27). Mesoscale physical processes such as local upwelling and anticyclonic eddies that shoal the oxic-anoxic boundary have been shown to enhance the development of SCMs (15,16).…”
Section: Resultsmentioning
confidence: 99%
“…Where light reaches the top of the OMZ, a low-light clade of Prochlorococcus is found in the ETSP 37 and Arabian Sea 38 and represents a clear example of differences in OMZ community composition that may be generated by shoaling 16 . Although earlier studies did not generate 16S rRNA sequences to which our data can be compared, we also identified Prochlorococcus OTUs in OMZ samples that were less abundant at shallower depths, as well as a Prochlorococcus OTU that may increase with deoxygenation ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In either case, where OMZs reach the base of the euphotic zone, low DO might reduce diversity among aerobes due to varying oxygen tolerances 10 . OMZ shoaling may also alter competition for resources-especially through availability of light within the OMZ, which could favour photoauto-and photohetero-trophs in the competition for nutrients and substrates 16 . Within the OMZ, further decreases in DO may favour particular groups and particular forms of metabolism.…”
mentioning
confidence: 99%
“…As NO 2 À oxidation can persist under o1 mM DO, NOB may directly compete with other organisms for NO 2 À in OMZs (Lipschultz et al, 1990, Fü ssel et al, 2012; in the ETNP OMZ, the accumulation of NO 2 À and its isotopic composition suggest that NO 3 À may be continually reduced and reoxidized through dynamic N and NO 2 À cycling (Casciotti and McIlvin, 2007). Adding to this complexity, OMZs are expanding as a consequence of climate change (Stramma et al, 2008, Keeling et al, 2010, potentially altering the rates and distribution of N transformations in the water column (Gilly et al, 2013). In the ETNP, N loss rates have varied severalfold over the past few decades in response to variations in the DO (Deutsch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%